PERSEPSI MASYARAKAT TENTANG ALTERNATIF PEMECAHAN MASALAH TRANSPORTASI DI JALAN RIAU KOTA PEKANBARU - M Taufik Nizam; Puji Astuti; Mardianto Manan (Center for Research and Community Service (LPPM) University of Abulyatama, 2016)
Riau street in Pekanbaru classified as secondary arterial roads with solid activit s so susceptible to the problem of traffic. The physical condition of damaged roads, land use mix and irregular, activities of right and left side crowded streets, parking inadequate, lack of public transport, and the behavior of road users who are not orderly, is the picture of the problem of traffic that occurs on the Riau street. This is supported also by the growth in the number of private vehicles. The accumulation of a variety of symptoms that led to the road capacity can no longer accommodate the volume of passing vehicles, causing traffic delays. One way to unravel this problem is to assess the public's perception of road users alternative solutions to problems related to urban transport in Riau street. The method used is descriptive quantitative with the number of respondents 100 people and supported by a statement from the policy holder of the traffic in the city of Pekanbaru . Public perception related factors causing transportation problems in Riau street is the traffic policy is less strict in discipline of road users, the traffic volume exceeds the capacity of the road, setting traffic light rigid, road users are not orderly, parking space is limited, public transport is limited, and the illegal parking. Alternative solutions is the increase in traffic policy, modify or regulate the flow of traffic, optimization of public transport facilities and infrastructure, restrictions on the use of private vehicles, road widening, traffic lights adjustment, socialization regulation and enforcement, and the construction of flyovers..